What a unicorn knows : how leading entrepreneurs use lean principles to drive sustainable growth - May, Matthew E.; Dominguez, Pablo (Business consultant) (Ascent Audio, 2023)
Why do some young companies become unicorns, while others don't? It's easy for scale-ups, giddy from early startup success, to get ahead of themselves and stumble. It's even easier to be slowed down by the many forces of resistance working against them: drag, inertia, friction, and waste. Drawing on a mastery of lean-based methods for achieving maximum effect with minimum means, private equity operators Matthew E. May and Pablo Dominguez provide listeners with a powerful framework of universally applicable principles that enable any company to effectively accelerate its ability to scale and grow. Called The Unicorn Model and built on five foundational principles, the authors deliver a compelling narrative of stories and experiences in an easy-to-remember mnemonic, S.C.A.L.E.: Strategic speed, Constant experimentation, Accelerated value, Lean process, and Esprit de corps. Drawn from the authors' successful track record in using S.C.A.L.E. with a wide variety of unicorn-level companies, What a Unicorn Knows offers a necessary guide for rapid but lasting growth.